A sediment fluxes investigation for the 2-D modelling of large river morphodynamics. (July 2015) - Guerrero, Massimo; Latosinski, Francisco; Nones, Michael; Szupiany, Ricardo N.; Re, Mariano; Gaeta, Maria Gabriella
Highlights: We investigated sediment fluxes in a bifurcation of the large Parana River. A 2-D numerical un-coupled model was applied to the bifurcation reach. Numerical experiments were performed to test the model reliability. The grid longitudinal spacing corresponded to the wave length of the observed dunes. The morphodynamic time step accounted for the observed river bars celerity. Abstract: A complete understanding of alluvial-bed dynamics is desirable for evaluating a variety of issues related to water resources. Sediment fluxes were investigated in a bifurcation of the large Parana River near Rosario, Argentina. The backscatter estimations from the Doppler profilers provided the suspended load of the sediment forming the riverbed. An echo-sounder was applied to track the dunes yielding the bed-load estimation. Aiming to show the usefulness of the recorded data, a 2-D numerical code was applied to the 10-km long and 2-km wide Rosario reach. The morphodynamic module was un-coupled from the hydrodynamics assessment, which enabled the long-term prediction of the river morphology accounting for the hydrological yearly variation with a quasi-steady approach. Numerical experiments were performed to test the sensitivity of the hydrodynamic model to the computational time-step and mesh size, to test the un-coupling scheme performance regarding the full-dynamic modelling, to test the accuracy of the sediment transport formulae based on the field evidence and, finally, to provide guidance to properly fix the model parameters.